Zeros of Convex Combinations of Elementary Families of Harmonic Functions - Jennifer Brooks; Megan Dixon; Michael Dorff; Alexander Lee; Rebekah Ottinger (Mathematics, 2023)
Brilleslyper et al. investigated how the number of zeros of a one-parameter family of harmonic trinomials varies with a real parameter. Brooks and Lee obtained a similar theorem for an analogous family of harmonic trinomials with poles. In this paper, we investigate the number of zeros of convex combinations of members of these families and show that it is possible for a convex combination of two members of a family to have more zeros than either of its constituent parts. Our main tool to prove these results is the harmonic analog of Rouché’s theorem.